Alcohol consumption among pregnant women in Northern Tanzania 2000–2010: a registry-based study - Isaksen, Alexander Blaauw (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Alcohol can be harmful to the development of the foetus. In most developed countries, pregnant women are recommended to abstain from alcohol, however in developing countries, women are less likely to receive these recommendations. With respect to pregnant women in Northern Tanzania, this study aims to 1) describe time trends in level of alcohol consumption, 2) assess socio-demographic predictors of alcohol consumption, and 3) describe associations between alcohol consumption and health-related maternal and foetal outcomes. METHODS: Data related to 34,090 births between 2000 and 2010 was obtained from the Medical Birth Registry at Kilimanjaro Christian Medical Centre (KCMC) in Moshi, Tanzania and analysed. Poisson regression analysis was used to assess associations between potential risk factors and alcohol consumption, and between alcohol consumption during pregnancy and maternal and foetal health outcomes. RESULTS: From 2000 to 2010, the proportion of women reporting alcohol consumption during pregnancy decreased from 49.5 to 21.5 %. The socio-demographic predictors most strongly related to alcohol consumption were religion (Catholics 53.6 %, Protestants 25.9 %, Muslims 14.8 %) and tribe (Chaggas 45.2 %, Pares 17.3 %, Maasais 6.6 %). Pregnant women consuming alcohol were more likely to be older, taller, and have higher pre-pregnancy body mass index, and were less likely to present with anaemia (Hb < 11.0 g/dl) at last antenatal care (ANC) visit/at admission; adjusted relative risk (ARR) 0.84 (95 % confidence interval 0.79–0.90) for alcohol consumption vs. abstinence. Maternal alcohol consumption during pregnancy was associated with a decreased risk of being small for gestational age (ARR 0.87 (0.80–0.94) and a decreased risk of gestational age less than 37 weeks (ARR 0.89 (0.81–0.99). CONCLUSIONS: The proportion of pregnant women reporting alcohol consumption decreased by 56.5 % from 2000 to 2010. Alcohol intake was strongly associated with socio-demographic factors. The association between alcohol intake and favourable perinatal outcomes remained significant after maternal factors were adjusted for. Information on diet, lifestyle factors and maternal health might give further insight into this unexpected observation. The proportion of pregnant women consuming alcohol in Northern Tanzania is high, and greater awareness of health outcomes associated with alcohol consumption is advised.